Faktor-Faktor yang Mempengaruhi Keputusan Stock Split dan Dampaknya terhadap Nilai Perusahaan - Muammar Khaddafi; Nurul Safitri; Resa Odina; Salima Salima (International Forum of Researchers and Lecturers, 2026)
Stock split is a corporate policy commonly undertaken by public companies to change the number of outstanding shares without altering the total value of equity. This study aims to conceptually examine the factors that drive a company's decision to conduct a stock split and to analyze its impact on firm value. The method used is a literature review by examining prior research findings and relevant theoretical frameworks, namely signaling theory and trading range theory. The results indicate that the stock split decision is influenced by the stock price level (price to book value), the company's financial performance, stock trading liquidity, and firm size. On the other hand, stock split s are shown to provide a positive signal to the market, reflected in increased trading volume activity and potential abnormal returns around the announcement date, although the effect on the company's fundamental value is indirect and functions mainly as an information signal. The implication is that management needs to carefully consider stock price conditions and financial performance before deciding on a stock split so that the signal conveyed to the market can be interpreted positively by investors.